Volver a la ternura - Bazán Gayoso, Elizabeth (2011)
The tenderness is an inherent affective potential element inherent to the human structure, fundamental in the personal, family and social development process. Its early presence in the early maternal relationship will be reflected subsequently in a healthy personality, capable to face challenges and conflicts. The tenderness as a care leads us to the concrete of the life and is an alternative response in view of the hearth hardness and the social indifference. Its historic and prophetic hardness is capable to transform interhuman relationships. We have the responsibility to communicate this tenderness by fidelity to ourselves and others. It is in our hands to return into it, recreate it.